Report of Non Syndromic Mental Retardation In Three Sisters - Alireza Moghadas (Ravānshināsī-i Afrād-i Istis̠nāyī, 2011)
This case report is Significantly important, Due to the fact, that so far no documeted report has shown the presence of three female members of the same family having mental retardation. History and Mental  status examination and physical examination was taken and the diagnosis was undertaken according to DSM IV-TR. Incidence of Mental Retardation is estimated about 1-3% in normal Population at any time (schaefer 2010). This disorder is 1.5 times more common in men than women (Sadock, 2007). Mental Retardations occure secondary to genetics, developmental, acquired or combination of these causes (Sadock, 2007). But what is rare and unusual is the fact that three Sisters are affected by mental Retardation in one and the same Family. There are some reports of new presentation and Etiology of Mental Retardation in medical literature (phadke, 2010). In this paper we will discuss and study different biological, social and cultural aspects of Mental Retardation and Present some mechanisms for primary prevention as well.